Evaluasi SPO Penggunaan Tracer Untuk Mengendalikan Missfile Berkas Rekam Medis di Bagian Filing UPTD Puskesmas I Denpasar Selatan: SOP Evaluation of The Use of Tracer to Control Medical Record Missfiles in The Filing Section of UPTD Puskesmas I Denpasar Selatan - Adiningsih, Luh Yulia; Romansyah, Deva Eddy; Kanaya, I Gusti Ayu Kade Yuli (Bali Medika Jurnal, 2021)
One of the management and quality of public health center services can be seen from the medical record file storage system in the Medical Record Unit. Based on observations at the UPTD Puskesmas I South Denpasar, it shows that there are still missfiles medical record files when they are taken and taken by medical record officers because medical records are not used to using a tracker, which has been in implementation since a month ago. Tracer is a tool as a medical record file that comes out. This study aims to see the evaluation of the evaluation of the Tracer Standard Operating Procedure (SOP) in the filing section of the UPTD Puskesmas I, South Denpasar. This type of research is an observational study with a descriptive design that describes the phenomena found. The subjects in this study were three medical record officers, one graduate of Bachelor of Nursing and two high school graduates. The object of this research is the SOP tracer in the filing section. The results showed that 30% of the officers had not performed according to the SOP to use already in the UPTD Puskesmas I South Denpasar.